2004
DOI: 10.1063/1.1831568
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and Hall effect of free-standing highly resistive epitaxial GaN:Fe substrates

Abstract: Free-standing highly resistive Fe-doped GaN layers grown by hydride vapor phase epitaxy were characterized by temperature-dependent conductivity and Hall effect measurements. Samples with a room-temperature resistivity of 1.6×107–6×108Ωcm and a Hall mobility of ∼330cm2V−1s−1 showed simple band conduction with the mobility power x=−1.5 and an activation energy 0.58–0.60eV, which can be attributed to a Fe acceptor. Samples with a lower mobility, ⩽10cm2V−1s−1, exhibited an increase of the mobility with temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…4(b)], Fe-doped GaN is a semiconductor with a much smaller bandgap (∼ 0.6 eV) than pure GaN, in agreement with the experimental data of a small activation energy (0.58-0.60 eV) in Fe-doped GaN attributed to a Fe acceptor. 33 Spin calculations are also consistent with fix-spin-magnetic calculations of the ground state DOS. 6 The partial DOS of GaN and Fe-doped GaN in the lower panel of Fig.…”
Section: Investigations Of Magnetism In Diluted Magnetic Semiconductosupporting
confidence: 69%
“…4(b)], Fe-doped GaN is a semiconductor with a much smaller bandgap (∼ 0.6 eV) than pure GaN, in agreement with the experimental data of a small activation energy (0.58-0.60 eV) in Fe-doped GaN attributed to a Fe acceptor. 33 Spin calculations are also consistent with fix-spin-magnetic calculations of the ground state DOS. 6 The partial DOS of GaN and Fe-doped GaN in the lower panel of Fig.…”
Section: Investigations Of Magnetism In Diluted Magnetic Semiconductosupporting
confidence: 69%
“…[1][2][3][4] As in other III-V semiconductors, transition metals containing a number of d electrons close to five ͑Cr, Mn, Fe͒ behave as deep acceptors, like Fe in InP, 5 and can be useful for compensating unintentional donors. [1][2][3][4] As in other III-V semiconductors, transition metals containing a number of d electrons close to five ͑Cr, Mn, Fe͒ behave as deep acceptors, like Fe in InP, 5 and can be useful for compensating unintentional donors.…”
Section: Introductionmentioning
confidence: 99%
“…cathodoluminescence provided a binding energy of Fe-hole complex E a E0.24 eV for GaN:Fe [4]). Temperature-dependent conductivity and Hall studies [13] showed in counterpart that good-quality freestanding GaN:Fe is very weakly ntype, and in such a case E a E0.6 eV. On the other hand, the same group could not measure carrier origin in our MD specimens, and deduced E a from resistivity to be 0.2-0.3 eV [14].…”
Section: Article In Pressmentioning
confidence: 97%